PENGARUH PEMBERIAN PUPUK KANDANG SAPI DAN POC AIR CUCIAN BERAS TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PAKCOY (Brassica rapa L.) - Sigalingging, Lamria; Sembiring, Desi Sri Pasca Sari; Armaniar, Armaniar (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
Pakchoy (Brassica rapa) is a leafy vegetable belonging to the Brassicaceae family (cruciferous vegetables) and is known for its high economic value. This study aimed to determine the effect of cow manure fertilizer and liquid organic fertilizer (LOF) made from rice washing water on the growth and yield of pakchoy plants. The research was conducted at Jl. Komisi C, Pulo Brayan Bengkel Baru, Medan Timur District, Medan City, North Sumatra. A Factorial Randomized Block Design (RBD) was used, consisting of two treatment factors. The first factor was cow manure fertilizer (S) with four levels: S0 = 0 g, S1 = 375 g, S2 = 500 g, and S3 = 625 g. The second factor was rice washing water LOF (B) with four levels: B0 = 0 ml/L, B1 = 150 ml/L, B2 = 250 ml/L, and B3 = 350 ml/L. There were 16 treatment combinations, each replicated three times. The results showed that the most effective treatment was the combination of S3 and B3, using 625 g of cow manure and 350 ml/L of liquid organic fertilizer, which significantly improved the growth and productivity of pakchoy. Application of cow manure fertilizer had no significant effect on plant height and number of leaves but had a significant effect on leaf width and a highly significant effect on stem diameter and plant weight. Meanwhile, the application of rice washing water LOF had no significant effect on plant height, number of leaves, leaf width, or stem diameter, but showed a significant effect on plant weight.